A Case of Combined Periodontal and Prosthetic Treatment for Enamel Hypocalcification - Ide, Takako (Nihon Hotetsu Shika Gakkai Zasshi, 2006)
Patient: A 23-year-old female was seen with a major complaint involving problems of esthetic and masticatory function, since her posterior teeth had collapsed due to enamel hypocalcification. Radiographic examination suggested that many teeth were affected by periodontitis apicalis. Discussion: Combined periodontal and prosthetic treatments including a crown lengthening procedure enabled us to fabricate esthetic and functional restorations. Conclusion: The crown lengthening procedure sometimes involves the loss of alveolar bone. In this case, however, the treatments were successful owing to the sufficient volume of bone available. As a result, the prosthesis achieved optimal plaque control. This clinical report describes the effectiveness of the periodontal and prosthetic treatments for enamel hypocalcification.